Romantic Relationships in Young People with Long-Term Health Conditions: A Scoping Review. (11th December 2020) - Jordan, Abbie; Carter, Bernie; Forgeron, Paula; Fournier, Karine; Sanders, Kate
Abstract: Objective: Forming and maintaining romantic relationships is an important developmental task in adolescence and young adulthood. This scoping review seeks to explore how young people with long-term physical health conditions understand and experience romantic relationships. Methods: Using Arksey and O'Malley's scoping review framework, a systematic search of five databases was conducted (PsychINFO, Cinahl, MEDLINE, Embase, and Web of Science). Studies were eligible for inclusion in the review if they were published in peer-reviewed journals, used primary data collection methods, and adopted quantitative, qualitative, or mixed-methods approaches to study romantic relationships in 11–25 year olds with long-term physical health conditions. Using a data extraction form, data pertaining to demographic characteristics of young people with long-term physical health conditions and relationship engagement were extracted from eligible papers. Results: Searches returned 4645 papers after duplicate removal, with a two-stage screening process resulting in 111 full-text papers being reviewed. Thirty-three eligible papers were included across a range of long-term physical health conditions. Findings identified that living with a long-term physical health condition impacted young people's perceptions and experiences of romantic relationships across the relationship lifespan, from envisaging future relationships, to forming relationships, and sustaining relationships. Issues around body confidence and self-esteem were identified as challenging in terms of perceptions and experiences of romantic relationships. Conclusions: Findings demonstrate that young people wish to engage with romantic relationships, yet many report particular challenges associated with forming and sustaining relationships due to the constraints of their condition and treatment. Future research should consider nonheterosexual relationships.